Radiocarbon ages of NW Himalaya peat record during 4.2 ka event - Singh, Dharmendra Pratap; Paul, Kaustav; Pawar, Rahul; Rai, Soni; Mohanty, Ranjan Kumar; Laksar, Amzad Hussain; Maurya, Abhayanand Singh (PANGAEA, 2026)
This dataset contains high-resolution geochemical measurements from the CT-02 alpine peat profile collected from the Chandra Valley, northwestern Himalaya, Himachal Pradesh, India (32.472022° N, 77.612433° E; 4309 m a.s.l.). The 44 cm peat sequence spans approximately 5.6 to 1.0 ka BP and was sampled at 1 cm intervals. The chronology is constrained by six AMS radiocarbon dates obtained from bulk peat organic carbon and calibrated using the IntCal20 calibration curve; an age-depth model was constructed using the Bayesian Bacon approach.
Keywords: d13C; Himalayas; Peat